Comprehensive prevention and control technologies for karst tunnel construction safety: integration of advanced forecasting, monitoring, and emergency response - Yaodong Luo; Bing Luo; MingJun Li; Tiansi Zhang; Shaoping Yang; Luyao Ma; Bihe Zhang; Haoyan Zhang; Saeed Rehman (Carbonates and Evaporites, 2026)

A composite catalytic reforming electrode with perovskite catalyst and Ni foam for high efficient CH4-fueled solid oxide fuel cell - Wei Luo; Yong Yang; Qinzhong Chen; Mingjun Li; Peng Qiu; Manqing Yang; Kang Li; Yangbo Jia; Renhong Li; Tong Wei (Chemical Engineering Journal, 2026)

Enhancing soil ecosystem multifunctionality via carbon input and enzymatic catalysis in cover crops under antibiotic contamination - Ju Wang; Huanhuan Zhang; Jintao Yu; Xuechen Zhang; Mingjun Li; Peizhi Yang; Ziyan Li (Applied Soil Ecology, 2026)

Stability assessment of CO2 hydrate in marine sediments using millennial-scale methane hydrate as a natural benchmark - Lei Zhang; Wei Song; Yuanyuan Cui; Pengfei Wang; Mingjun Yang; Bingbing Chen; Yongchen Song (Journal of Environmental Chemical Engineering, 2026)

Seepage-path-dependent CO2 hydrate formation and storage capacity enhancement in NGH reservoirs - Ziming Yang; Lei Zhang; Yufeng Jiang; Bingbing Chen; Mingjun Yang (Fuel, 2026)

RBM10 suppresses porcine epidemic diarrhea virus replication by degrading nonstructural protein 3 through selective autophagy - Mingyu Liu; Zhenpeng Tang; Huixin Zhu; Jinxiu Lou; Yangyang Zhang; Mingjun Ye; Yufan Xu; Juan Bai; Ping Jiang; Zhen Yang; Gongguan Liu; Xianwei Wang (Veterinary Microbiology, 2026)

Integrated multi-omics reveals divergent salt stress response mechanisms in three alfalfa (Medicago sativa L.) cultivars - Yue Wang; Wenli Wu; Fenfen Liang; Taotao Zhao; Shaowei Li; Mingjun Yang; Feifan Leng; Xinqiang Zhu; Xiaoli Wang (Plant Science, 2026)

Quantifying evaporative water loss in semi-arid urban lakes based on daily isotope measurements - Yinmei Yang; Shengjie Wang; Yudong Shi; Hongyang Li; Shijun Lei; Yujiao Zhang; Jianwen Zhao; Xiaofan Zhu; Mingjun Zhang (Journal of Hydrology, 2026)

Using stable isotopes in water vapor to identify the onset date of the East Asian summer monsoon over the Loess Plateau - Yujiao Zhang; Yudong Shi; Shengjie Wang; Hayoung Bong; Kei Yoshimura; Shijun Lei; Meng Xing; Yinmei Yang; Jianwen Zhao; Mingjun Zhang (Journal of Hydrology, 2026)

Structural and operational optimization of cold storage system for enhanced energy efficiency, rapid cold release and economic benefits - Yuan Lv; Zhimei Zuo; Zizhuang Ma; Wang Cheng; Fan Wang; Chuanxiao Cheng; Zheng Ling; Lanlan Jiang; Tao Yu; Mingjun Yang; Lei Yang; Yu Liu; et al. (Journal of Cleaner Production, 2026)

Cooling-regime regulation of rutile crystallization and enrichment in titanium-bearing electric arc furnace slag - Wanlong Fan; Zhiwei Peng; Fengming Yang; Huixian Bai; Jianzhi Zhang; Lingyun Yi; Mingjun Rao (Process Safety and Environmental Protection, 2026)

Modeling Hydrate Formation Kinetics and Permeability Evolution: A New Approach Integrating Different Gas-Liquid Contact Modes - Yongqiang Xia; Bingbing Chen; Lanlan Jiang; Lei Yang; Mingjun Yang; Tao Yu; Yongchen Song (Gas Science and Engineering, 2026)

Mobile self-assembled membranes: A novel strategy for boosting light hydrocarbon separation efficiency - Yanan Jia; Zixuan Huang; Minglong Wang; Zhi Li; Hongyi Yu; Jun Xu; Bei Liu; Mingjun Deng; Jingming Li; Kun Li; Mingke Yang; Ruihang Zhang; et al. (Chemical Engineering Journal, 2026)

Crystal-phase-mediated synthesis of niobium carbide from model niobium-bearing phases via a pyrochlore intermediate - Shaoyang Chang; Boqi Wang; Mingjun Rao; Zhao Yang; Zhongshuai Jia; Haijiao Xie (Minerals Engineering, 2026)

Sustainable pre-reduced sinter production: Recycling carbon-bearing dust and reducing CO2 emissions - Jing Wang; Xiduan Yang; Hui Xu; Laisheng Li; Boqi Wang; Jinliang Xiong; Xinyue Wu; Huibo Liu; Liangping Xu; Mingjun Rao (Journal of Cleaner Production, 2026)

Ah-level small-molecule proton batteries enabled by a cost-effective gradient-porous composite separator - Yu Li; Rui Li; Xinyu Wang; Mengxiao Li; Junjie Wang; Huige Ma; Mengjing Wu; Haiping Yu; Bei Wang; Huijie Wang; Mingjun Hu; Jun Yang (Chemical Engineering Journal, 2026)

Electrostatic interaction induced enhancement of conductive hydrogel for motion detection and targeted identification of ascorbic acid in sweat - Jiarui Liu; Xianghe Zheng; Xinhang Yu; Mingjun Jia; Kai Wei; Liangjiu Bai; Wenxiang Wang; Kun Yin; Lixia Yang; Hou Chen (Analytica Chimica Acta, 2026)

Direct operation or delegation? Post-concession port infrastructure governance under risk preference and demand volatility - Minghua Xiong; Weiting Yang; Jiancong Liang; Mingjun Zhan (Frontiers in Marine Science, 2026)
Public-private partnership, or PPP, is now widely adopted for developing port infrastructure worldwide. As these PPP projects near the end of their concession periods, governments are confronted with a key strategic challenge: achieving smooth transition and sustainable operation for these mature infrastructure assets. This paper centers on the core governance decision for post-concession port infrastructure—whether governments should take direct charge of operation or delegate management to private entities—and develops a strategic decision-making framework that fully accounts for private operators’ diverse risk attitudes (ranging from conservative to aggressive) and the inherent volatility of market demand. We first define the First-Best social welfare benchmark corresponding to direct public operation through theoretical analysis, then model the delegated operation mode as a classic principal-agent problem. Our analytical results confirm that the operator’s risk preference is the intrinsic root cause of operational decision distortions (in terms of service price and service level) under delegation, while market environmental uncertainty acts as a synergistic factor that amplifies such deviations, ultimately leading to service degradation and reduced maritime supply chain resilience. The core contribution of this study lies in deriving an optimal risk-contingent regulatory mechanism: we find that the per-unit subsidy must serve as a dynamic incentive and risk-hedging tool, with its parameter settings directly tied to the operator’s risk preference and demand volatility, so as to accurately offset the misalignment of private operational behaviors and ensure the achievement of socially optimal output levels. Most importantly, we establish a specific governance viability threshold: delegated operation is only optimal when the private sector’s operational efficiency advantage is substantial enough to outweigh the social welfare friction costs caused by risk-driven distortions; otherwise, reverting to direct public operation yields superior social and economic outcomes. This research provides maritime regulators with a prescriptive toolkit for managing the critical transition period of port asset governance.

Visual and quantitative insight into formation characteristics and sealing effect of CO2 hydrate cap in porous media with fracture channel - Guojun Zhao; Jia-nan Zheng; Yongchen Song; Zijun Feng; Ranjith Pathegama Gamage; Mingjun Yang (Journal of Cleaner Production, 2026)

Quality optimization and shelf-life prediction of braised beef using synergistic ε-polylysine-integrated sterilization technologies - Jingrong Cheng; Zhenhua Shi; Xueming Liu; Huaigu Yang; Xuping Wang; Yaosheng Lin; Mingjun Zhu; Daobang Tang (Food Control, 2026)

The AhR/ROS-mediated lipid peroxidation pathway contributes to 6PPDQ-induced intestine-specific injury in zebrafish during embryonic development - Zhe Wang; Yao Hu; Mingjun Zhu; Xinyue Yang; Qiancheng Huang; Anying Zhang; Xinyan Wang; Hong Zhou (Fish & Shellfish Immunology, 2026)

Multilayer-like peptide-lipid nanoparticles enable effective p53 mRNA delivery for tumor suppression in non-small cell lung cancer - Zhe Wang; Weisi Yuan; Meiping Song; Mingjun Zhang; Chunpeng Yang; Weibang Xia; Jiao Chen; Yuhong Zhen; Yu Liu; Hongxu Liu; Yunming Wang; Yinan Zhao; et al. (Chemical Engineering Journal, 2026)

CTAB regulated front-end synthesis of schwertmannite for rapid high-capacity as(III) removal with structure evolution and mechanistic insights - Mingjun Zou; Yajing Chen; Linlin Tong; Hongying Yang (Chemical Engineering Journal, 2026)

Effects of low-molecular-weight organic acids and manganese-modified biochar application sequences on the environmental risk of soil cadmium and arsenic - Yongqiang Yang; Mingjun Li; Yipan Zhao; Liping Li; Yale Wang; Weiqin Xing; Chunhong Xu; Qipo Yang; Yali Wang; Yu Liu (Environmental Geochemistry and Health, 2026)

Hydrate stability assessment in marine environments: Implications for CO2 sequestration site optimization - Lei Zhang; Wei Song; Fei Huang; Bingbing Chen; Huiru Sun; Mingjun Yang (Journal of Environmental Chemical Engineering, 2026)

Quality deterioration and metabolic regulation during hot-air drying of Rheum palmatum L.: an integrated analysis of physiology, drying kinetics, non-targeted metabolomics, and enzyme activity dynamics - Wen Luo; Yingying Chen; Jia Zhou; Mingjun Yang; Yonggang Wang (Physiology and Molecular Biology of Plants, 2026)

Temperature-driven regime shifts in riverine bacterial communities: Machine learning identifies key thresholds and seasonal management implications - Ru Liu; Peng Wang; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang; Qinwei Chen; Wei Yang (Journal of Environmental Sciences, 2026)

Is expectation disconfirmation related to stakeholder satisfaction and willingness to engage in national parks? A case study of Shennongjia National Park in China - Yangyang Zhang; Zhen Fu; Yang Xiang; Chucai Peng; Mingjun Teng; Lixiong Zeng; Wanji Yang; Lei Pan; Pengcheng Wang (Forest Policy and Economics, 2026)

Enhanced stability and bioavailability of astaxanthin via piperine co-encapsulation in whey protein fibril- sodium alginate complexes - Jingrong Cheng; Junquan Zheng; Xueming Liu; Huaigu Yang; Xuping Wang; Yaosheng Lin; Mingjun Zhu; Daobang Tang (Carbohydrate Polymers, 2026)

Study on mining pressure law and its influencing factors of deep super-long gangue backfilling working face - Yang Kang; Zhang Qiang; Zou Mingjun; Cui Pengfei; Zong Tingcheng; Zhang Bin; Lv Haonan; Bai Yu; Deng Panbo; Li Jiang (Arabian Journal of Geosciences, 2026)

Epidemiology of Isoparorchis eurytremus (Trematoda: Isoparorchiidae) Infection in Southern Catfish (Silurus meridionalis; Siluriformes: Siluridae): A Case Study in the Dongting Lake, China - Dong Liu; Xiangrong Liu; Mingjun Yan; Naige Fu; Wei Wan; Gang Xu; Qianqian Ku; Xin Yang; Bo Hong; Chongrui Wang; Dongsheng Ou; Xiping Yuan (Fishes, 2026)
Parasitic infections pose a significant threat to the wild population of Southern catfish (Silurus meridionalis) in Dongting Lake, yet the specific pathogen identity and epidemiological drivers remain unclear. This study combined morphological assessment, 28S rDNA molecular identification, and Generalized Linear Models (GLM) to elucidate the infection dynamics and pathogenicity of trematodes. Molecular analysis confirmed the pathogen as Isoparorchis eurytremus. GLM analysis revealed that apparent spatiotemporal variations in infection were actually sampling bias in fish host size structure; the total length was identified as the decisive predictor of infection risk. The infection probability followed a sigmoid growth pattern with a median infection length (L50) of 70.4 cm, a phenomenon attributed to the host’s ontogenetic diet shift from insectivory to obligate piscivory. Anatomical observations indicated that the infection induced systemic pathology; beyond severe fibrosis and mechanical damage to the swim bladder, varying degrees of parenchymal lesions were evident in the liver, spleen, and kidney. These findings indicate that I. eurytremus infection in S. meridionalis is a size-dependent, accumulative process maintaining a homogenous high pressure across the lake ecosystem, necessitating a shift in perspective from localized lesions to systemic disease management.

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

CO2 injection strategies to enhance the sequestration capacity in oceanic reservoir for hydrate-based carbon storage - Xinru Wang; Jing Chen; Huiru Sun; Bingbing Chen; Xin Lv; Weixin Pang; Yongchen Song; Mingjun Yang (Fuel, 2026)

Sustainable soil management in acidic paddy fields: liming and biochar application reduce greenhouse gas emissions while enhancing rice yields - Gong Wu; Xiaoyu Wang; Xing Wei; Mengyou Zhang; Jiangseng Chu; Mingjun Hou; Leili Lin; Yang Chen; Zhao Che; Xiaoxiao Li; Can Zhang; He Song (Journal of Environmental Management, 2026)

Effect of modified EVA-GMX bionic nanocomposite pour point depressants on the rheological properties of waxy crude oil - Bingfan Li; Ziyuan Guo; Liming Zheng; Mingjun Du; Jiang Han; Chao Yang (Fuel, 2026)

Stability assessment of CO2 hydrate-based sequestration in complex marine environments - Lei Zhang; Heng Liu; Xinyi Shan; Bingbing Chen; Mingjun Yang (Chemical Engineering Journal, 2026)

Continuous Removal of Fluoride by Fe/Al-Anchored Bamboo Charcoal in Fixed Bed Column and Prediction of Breakthrough Curve using Artificial Neural Network Model - Shuqin Bai; Ru Ya; Wei Ding; Xiaohua Xie; Mingjun Zhou; Guojing Zhao; Tianxu Yang (Water, Air, & Soil Pollution, 2026)

FishSegNet-PRL: A Lightweight Model for High-Precision Fish Instance Segmentation and Feeding Intensity Quantification - Xinran Han; Shengmao Zhang; Tianfei Cheng; Shenglong Yang; Mingjun Fan; Jun Lu; Ai Guo (Fishes, 2025)
Siniperca chuatsi, commonly known as mandarin fish, is one of the most economically valuable freshwater species in China. In 2022, the national aquaculture production of mandarin fish reached approximately 401,000 tons, accounting for a significant share of freshwater aquaculture in China and nearly dominating the global commercial farming landscape. With the rapid development of recirculating aquaculture systems (RASs), higher requirements have been raised for feeding efficiency and fish health monitoring. Traditional on-site visual observation methods are highly subjective, inefficient, difficult to quantify, and prone to misjudgment under conditions such as insufficient illumination, turbid water, or high stocking density. To address these challenges, this study proposes FishSegNet-PRL, an instance segmentation-based model designed to quantify the feeding intensity of mandarin fish. The model is built upon the YOLOv11-seg framework, enhanced with a P2 detection layer (P), a residual cross-stage spatial–channel attention module (RCSOSA, R), and a lightweight semantic-detail-enhanced cascaded decoder (LSDECD, L). These improvements collectively enhance small-target detection capability, boundary segmentation accuracy, and real-time inference performance. Experimental results demonstrate that FishSegNet-PRL achieves superior performance in mandarin fish instance segmentation, with a Box mAP50 of 85.7% and a Mask mAP50 of 79.4%, representing improvements of approximately 4.6% and 13.2%, respectively, compared with the baseline YOLOv11-seg model. At the application level, multiple feeding intensity quantification indices were constructed based on the segmentation results and evaluated, achieving a temporal intersection-over-union (IoUtime) of 95.9%. Overall, this approach enables objective and fine-grained assessment of mandarin fish feeding behavior, striking an effective balance between accuracy and real-time performance. It provides a feasible and efficient technical solution for intelligent feeding and behavioral monitoring in aquaculture.

Disclosing occurrence of typical tire wear particle-derived chemicals in grassland soils from remote pastoral areas, north China - Guoguang Wang; Aoduo Yang; Shuaihao Liu; Mingjun Mo; Haiyue Chen; Guangzhi Rong; Haixia Wang; Yu Liu (Environmental Research, 2025)

CTAB-mediated in situ synthesis of schwertmannite for enhanced As(V) removal from arsenic-contaminated wastewater: performance and mechanistic insights - Mingjun Zou; Yajing Chen; Linlin Tong; Zhenan Jin; Hongying Yang (Chemical Engineering Journal, 2025)

Ultra-short-term wind speed hybrid forecasting model based on maximal information coefficient-optimized TVF-EMD and resTKAN - Chenglin Yang; Wenyu Zhang; Jing Ren; Guoyin Wang; Yining Ma; Mingjun Li (Earth Science Informatics, 2025)

Rapid visual field detection of Pratylenchus coffeae in yam tissues via RPA-CRISPR/Cas12a - Weichao Zhao; Mengli Lin; Yulong He; Jin Gao; Jiangli Zhang; Mingjun Li; Qingxiang Yang (Crop Protection, 2025)

Genome-wide investigation and functional analysis of 20S proteasome subunits in Locusta migratoria - Yong Yang; Qinyao Zhu; Mingjun Wang; Wenhui Guo; Xiaohong Zhang; Daochuan Zhang (Pesticide Biochemistry and Physiology, 2025)

Forest restoration regulates the ecosystem service supply-demand relationship in a mountainous small watershed - Ting Yang; Xiaowei Nie; Jiaoyang Xu; Bing Wang; Mingjun Teng; Pengcheng Wang (Journal of Environmental Management, 2025)

Multifunctional scaffolds based on 3D printing for spinal cord and peripheral nerve defect repair - Xinran Chen; Mingjun Wu; Jie Zhang; Pengxiang Yang; Jiahui Guo; Xiaosong Gu; Xiu Dai (Chemical Engineering Journal, 2025)

“Peeling egg” strategies for regenerating spent graphite with tailored surface/sub-surface and removed impurities towards high capacity - Tianjing Wu; Chen Liu; Mingjun Jing; Wei Sun; Yue Yang; Honghui Hu; Peng Ge (Chemical Engineering Journal, 2025)

Investigating the regulatory role of seasonal changes in soil and microbial communities on Codonopsis pilosula physiology - Ning Zhu; Yumeng Zhou; Mingjun Yang; Feifan Leng; Xiaoxu Lv; Jixiang Chen; Wen Luo; Yonggang Wang (Biocatalysis and Agricultural Biotechnology, 2025)

From stainless steel to batteries: industrial-scale closed-loop hydrometallurgical integration for ferronickel-to-precursor conversion - Jun Luo; Pengfei Yang; Jing Chen; Yanhu Chen; Mingjun Rao; Guanghui Li; Tao Jiang (Journal of Cleaner Production, 2025)

Double-confined FeCo nanoalloys as efficient and stable catalyst for selective hydrogenation of nitroarenes - Zhenyu Lei; Hao Sun; Lin Wu; Honglei Sun; Xiaomin Yang; Jingyao Liu; Peng Zhang; Mingjun Jia (Chemical Engineering Journal, 2025)

Biocontrol of the black-spot disease pathogen (Alternaria alternata) in Dioscorea opposita by native endophytic bacterium Bacillus sp. E-Do8 - Chaochuang Li; Longlong Ma; Houmin Wang; Shunpeng Li; Ruifei Wang; Hao Zhang; Mingjun Li; Qingxiang Yang (BioControl, 2025)

Leaf spot of yam caused by Schizophyllum commune in China - Ruifei Wang; Xuejia Wang; Liping Zhan; Xueyang Ren; Haibing Li; Yulong He; Hao Zhang; Yongkang Liu; Mingjun Li; Guixiao La; Qingxiang Yang (Australasian Plant Pathology, 2025)

Promotion of grain growth via solvent fumigation for wide-bandgap perovskite solar cells with low VOC deficit and perovskite/TOPCon tandem solar cells with efficiency >30% - Xiang Liao; Yuanfang Zhang; Zijian Qu; Qiang Zeng; Mingjun Zhang; Jungan Wang; Yining Pan; Jie Yang; Damin Zheng; Zengsheng Liu; Linhong Li; Menglei Xu; et al. (Science Bulletin, 2025)

Knockdown of LmSPARC influences lipid metabolic homeostasis involved ovarian development in Locusta migratoria - Mingjun Wang; Wenhui Guo; Yong Yang; Qingyao Zhu; Xiaohong Zhang; Daochuan Zhang (Journal of Insect Physiology, 2025)

Engineering B₄O₇2−-cross-linked double‑carbon layer separators for mitigating molecular shuttle in rechargeable small-molecule batteries - Xinyu Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Mingsheng Yang; Bei Wang; Haiping Yu; Mengxiao Li; Yuxin Hao; Zhihui Wang; Jingru Liu; Mingjun Hu; et al. (Chemical Engineering Journal, 2025)

Identification and utilization of a novel large-effect QTL and linked markers for enhancing protein concentration in peanut - Mingjun Wang; Jianbin Guo; Gaorui Jin; Taihua Yang; Weigang Chen; Yuning Chen; Li Huang; Huaiyong Luo; Xiaojing Zhou; Boshou Liao; Huifang Jiang; Nian Liu; et al. (Theoretical and Applied Genetics, 2025)

Construction of a new multi-layer stacked model for precipitable water vapor prediction - Bingyan Li; Zhenping Shao; Kequan Zhang; Mingjun Li; Chenglin Yang; Wenyu Zhang (Theoretical and Applied Climatology, 2025)

Physiological and Transcriptomic Analyses Reveal Anthocyanin Coordinately Regulate Saline-Alkali Stress in Dioscorea Opposita - Chaochuang Li; Shunpeng Li; Longlong Ma; Houmin Wang; Hao Zhang; Ruifei Wang; Jin Gao; Mingjun Li; Qingxiang Yang (Journal of Soil Science and Plant Nutrition, 2025)

Toad’s survivability and soil microbiome alterations impacted via individual abundance - Tian Zhang; Yang Liu; Junde Li; Mingjun Yuan; Chunhan Qiao; Xiao Huang; Xueyao Yang; Bo Gao; Chuan Lou; Yan Yang; Yu Cao (Biologia Futura, 2025)

Evaluation of the management of rotator cuff injuries utilising superparamagnetic iron oxide tracking stem cells - Ziang Cheng; Dianwei Liu; Jin-Young Park; Xiangji Meng; Yuxia Yang; Mengbo Dang; Xiaomei Dai; Jian Yang; Meijuan Yuan; Mingjun Li; Liang Wang; Yao Huang; et al. (Tissue and Cell, 2025)

Thermodynamic and kinetic studies of CO2 hydrate stability in complex deep-oceanic environments - Lei Zhang; Ziming Yang; Yang Ge; Bingbing Chen; Huiru Sun; Yongchen Song; Mingjun Yang (Process Safety and Environmental Protection, 2025)

Solventless selective self-condensation of cyclopentanone over robust TiO2-SnO2 acid-base bifunctional catalyst - Jiaqi Yan; Jingxuan Zhao; Jing Guo; Zhiyong Yang; Mingjun Xiong; Langsheng Pan; Yongfei Li (Journal of Environmental Chemical Engineering, 2025)

LC-MS/MS-based metabolomic of pink Auricularia cornea grown on Lycium barbarum sawdust substrate - Lei Ye; Xuezhen Yang; Zhenzhu Huang; Bo Zhang; Qing Tian; Yu Huang; Wei Tan; Mingjun Feng; Xiaolin Li; Hongbin Xu (Food Chemistry, 2025)

Regulating brønsted/lewis sites of facet-dependent cryptomelane-type MnO2 for simultaneously enhancing performance and N2 selectivity in NOx selective catalytic reduction with NH3 - Changye Mang; Jun Luo; Xiduan Yang; Mingjun Rao; Guipeng Yu; Guanghui Li; Tao Jiang (Chemical Engineering Journal, 2025)

Experimental research on the influence of wall effect on the structure of cumulated semi-cokes - Zhouzijing Yang; Peibin Zhang; Liying Zhang; Yuxiu Zhang; Xiangang Liu; Yuqiu Zhang; Haibo Gao; Yongqi Liu; Mingjun Sun; Yanxia Wang (Process Safety and Environmental Protection, 2025)

Spatial pattern of amount effect of daily precipitation isotopes in China: A consideration of seasonality based on observation and simulation - Yuqing Qian; Shengjie Wang; Mingjun Zhang; Kei Yoshimura; Hayoung Bong; Gahong Yang; Hongyang Li (Journal of Hydrology, 2025)

The role of clay in hydrate-based carbon emission reduction: Phenomenon, mechanisms, and application - Huiquan Liu; Shuai Wang; Yixuan Fu; Changrui Shi; Yongchen Song; Lunxiang Zhang; Cong Chen; Mingjun Yang; Zheng Ling (Fuel, 2025)

Long-term effects of emission reduction measures on PM2.5 sources and children’s lung function in Jinan, China - Deai Yang; Pengcheng Zuo; Mingjun Li; David Lim; Liangliang Cui; Zhihui Feng (Environmental Geochemistry and Health, 2025)

Associated effects of blood metal(loid) exposure and impaired glucose metabolism in patients with gastric precancerous lesions or gastric cancer - Yuting Zhu; Xiao Lin; Tingting Wang; Sheng Wang; Wuqi Wang; Mengran Ke; Yan Zhu; Bowen Zhang; Princess Ofosuhemaa; Yalei Wang; Mingjun Hu; Wanshui Yang; et al. (BioMetals, 2025)

A rapid and visual detection method for Alternaria alternata, the causal agent of leaf spot disease on yam, based on RPA-CRISPR/Cas12a - Yulong He; Chenwei Tong; Huixuan Chen; Weichao Zhao; Liping Zhan; Ruifei Wang; Jiangli Zhang; Jin Gao; Chaochuang Li; Mingjun Li; Qingxiang Yang (Physiological and Molecular Plant Pathology, 2025)

Application of biomass energy in titanomagnetite reduction for Fe/Ti recycling: Overcoming the challenge of iron grain growth - Lingyun Yi; Xiaoshuai Shen; Yang Shu; Bing Deng; Qiang Zhong; Zhiwei Peng; Mingjun Rao; Guanghui Li; Tao Jiang (Fuel, 2025)

Self-Reconstruction of ultralow-Pt-loading Co3O4 nanoneedle array cathode for high-performance Li-O2 battery - Yong Liu; Mingjun Han; Jianye Liu; Yaling Huang; Yisi Liu; Wenzhang Li; Yang Liu; Jie Li (Chemical Engineering Journal, 2025)

Thermoelectric performance in Ag2Se nanocomposites: The role of interstitial Ag and Pb orbital hybridization - Khak Ho Lim; Yuxuan Xia; Lixiang Xu; Mingjun Zhao; Mingquan Li; Ye Cheng; Jiale Mao; Shuang Wang; Lei Chen; Sai Wing Tsang; Pingwei Liu; Qingyue Wang; et al. (Chemical Engineering Journal, 2025)

Potential function of plant-growth-promoting endophytic Serratia fonticola CPSE11 from Codonopsis pilosula in phytoremediation of Cadmium ion (Cd2+) - Mingjun Yang; Yunxing Fu; Shu Hu; Feifan Leng; Yan Zhuang; Wenbin Sun; Yonggang Wang (Journal of Environmental Management, 2025)

Monolithic and effective kinetic promoter formed by immobilizing MWCNTs on cellulose for efficient hydrate-based gas storage - Shuai Wang; Huilian Sun; Zhen Li; Changrui Shi; Lunxiang Zhang; Mingjun Yang; Yanghui Li; Cong Chen; Yongchen Song; Zheng Ling (Chemical Engineering Journal, 2025)

Selection and validation of reference genes for the normalization of RT-qPCR gene expression data in Rheum tanguticum (Polygonaceae) under various abiotic stresses - Mingjun Yu; Jiarui Jin; Xiaoli Li; Yuping Liu; Xu Su; Marcos A. Caraballo-Ortiz; Penghui Zhang; Qian Yang; Rongju Qu; Zhaxi Cairang; Xuanlin Gao; Yinghui Zheng (Journal of Plant Physiology, 2025)

A sensitive geometric self-calibration method and stability analysis for multiview spaceborne SAR images based on the range-Doppler model - Lina Yin; Mingjun Deng; Yin Yang; Yunqing Huang; Qili Tang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Investigation of water blocking mitigation in a normal-pressure shale gas reservoir by high-temperature treatment: Insights from heat transfer range - Mingjun Chen; Xueni Chen; Yili Kang; Zheng Cheng; Lijun You; Gang Xiong; Dongsheng Yang; Chaozhong Qin (Fuel, 2025)

Rapid formation of carbon dioxide hydrate governed by the natural nano-clay for effective carbon dioxide capture - Huiquan Liu; Shuai Wang; Changrui Shi; Yongchen Song; Yixuan Fu; Zhen Li; Lunxiang Zhang; Cong Chen; Mingjun Yang; Zheng Ling (Fuel, 2025)

Contour-constrained branch U-Net for accurate left ventricular segmentation in echocardiography - Mingjun Qu; Jinzhu Yang; Honghe Li; Yiqiu Qi; Qi Yu (Medical & Biological Engineering & Computing, 2025)

Production characteristics and visualization insight of top/bottom depressurization exploitation of natural gas hydrate with overpressure gas - Guojun Zhao; Jia-nan Zheng; Guangjun Gong; Mingjun Yang; Yongchen Song (Fuel, 2025)

Oxidation and nitrosation in Cantonese sausage during processing and storage-The impact of adding Prunus mume polyphenol - Jingrong Cheng; Peiyu Chen; Xueming Liu; Daobang Tang; Huaigu Yang; Mingjun Zhu (Food Control, 2025)

Analysis of the genetic basis of fiber-related traits and flowering time in upland cotton using machine learning - Weinan Li; Mingjun Zhang; Jingchao Fan; Zhaoen Yang; Jun Peng; Jianhua Zhang; Yubin Lan; Mao Chai (Theoretical and Applied Genetics, 2025)

Thermodynamic and kinetic properties of gas hydrate phase transition from formation to decomposition with applications: A review - Zheyuan Liu; Xiaoyang Liu; Mingjun Yang; Weixin Pang; Binlin Dou; Yongchen Song (Journal of Environmental Chemical Engineering, 2024)

Visual study of hydrate particles agglomeration and rolling characteristic in gas-oil-water phase using a flow loop - Zheyuan Liu; Shichen Shen; Binlin Dou; Ni Liu; Liang Yang; Mingjun Yang; Yongchen Song (Fuel, 2024)

Structure identification and activity evaluation of polysaccharide from Codonopsis pilosula (C. pilosula nannf. Var. modesta (nannf.) L. T. Shen) - Mingjun Yang; Anxiang Wang; Xiaohui Tang; Xinjian Wang; Feifan Leng; Yonggang Wang (Food Bioscience, 2024)

Phase-Field Simulation of Counter-Current Imbibition and Factors Influencing Recovery Efficiency - Liu Yang; Mingjun Li; Haitao Zhang; Yan Liu; Zhaoyang Liu; Zhengyan Zhang; Fei Gong; Suling Wang (Transport in Porous Media, 2024)

Stress Distribution and Dynamic Evolution of Coal Surface Under a Single Droplet of Discrete Water Jet - Man Yuan; Xun Zhao; Mingjun Jiang; Yingke Liu; Fengchao Wang; Tengrui Yang; Lingxiao Yin; XiaoJiang Wen (Rock Mechanics and Rock Engineering, 2024)

Corrigendum to “Characteristics of microbial community during the different growth stages of yam (Dioscorea opposita Thunb. cv. Tiegun)” [Appl. Soil Ecol. 201 (2024) 105519] - Zhao Qin; Weichao Zhao; Haitao Ma; Jin Gao; Ruifei Wang; Chaochuang Li; Hao Zhang; Mingjun Li; Qingxiang Yang (Applied Soil Ecology, 2024)

Refining habitat selection for sulfate-reducing bacteria: Evaluating suitability and adaptability for sulfate-metal wastewater treatment during anaerobic-to-aerobic transitions - Zhendong Yang; Jing Wang; Qihong Wu; Zhaoyue Yang; Tuan Liu; Li Zeng; Zhaogang Lin; Mingjun Li; I.A. Ibrahim; Huaqun Yin; Zhenghua Liu (Journal of Environmental Management, 2024)

Behaviors of hydrate cap formation via CO2-H2O collaborative injection:Applying to secure marine carbon storage - Mingjun Yang; Mingyu Wu; Ziming Yang; Pengfei Wang; Bingbing Chen; Yongchen Song (Gas Science and Engineering, 2024)

Boosting oxygen reduction reaction kinetics by Fe–V dual sites in ultrafine V-Fe3C nanoparticles for aluminum-air batteries - Shuya Zhang; Qiming Chen; Qianqiao Wang; Xinyu Luo; Mingjun Cen; Wenchao Peng; Yang Li; Qicheng Zhang; Xiaobin Fan (Chemical Engineering Journal, 2024)

Scalable MXene/Sepiolite film-based hydrovoltaic generators with outstanding output power - Weijing Yuan; Huiquan Liu; Yixuan Fu; Yang Zhang; Haoqi Huo; Lunxiang Zhang; Mingjun Yang; Yanghui Li; Cong Chen; Yongchen Song; Zheng Ling (Chemical Engineering Journal, 2024)

External ligand-free nickel-catalyzed synthesis of polypyrazines towards stable, high-capacity and low-potential sodium ion storage - Zhihui Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Xinyu Wang; HaiPing Yu; Yuxin Hao; Yujie Dai; Huige Ma; Mengxiao Li; Hongwei Li; Mingsheng Yang; et al. (Chemical Engineering Journal, 2024)

Research Progress of the Sources, Distribution Characteristics, and Potential Risks of Microplastics in the Global Marine Environment - Jinnan Xiao; Xiuyuan Yang; Zhenming Zhang; Mingjun Wang; Zhaowen Yang; Xinrui Zhang (Water, Air, & Soil Pollution, 2024)

Dynamic patterns of particulate matter concentration and size distribution in urban street canyons: insights into diurnal and short-term seasonal variations - Xiaoshuang Wang; Xiaoping Chen; Zhixiang Zhou; Mingjun Teng; Yang Xiang; Chucai Peng; Chunbo Huang; Changhui Peng (Environmental Monitoring and Assessment, 2024)

Characteristics of microbial community during the different growth stages of yam (Dioscorea opposita Thunb. cv. Tiegun) - Zhao Qin; Weichao Zhao; Haitao Ma; Jin Gao; Ruifei Wang; Chaochuang Li; Hao Zhang; Mingjun Li; Qingxiang Yang (Applied Soil Ecology, 2024)

Copper induces cytotoxicity in freshwater bivalve Anodonta woodiana hemocytes - Mingjun Yan; Xiubao Chen; Tao Jiang; Junren Xue; Karsten Liber; Hongbo Liu; Jian Yang (Chemosphere, 2024)

RNAi-mediated glucose transporter 4 (Glut4) silencing inhibits ovarian development and enhances deltamethrin-treated energy depletion in Locusta migratoria - Mingjun Wang; Ningxin Yang; Wenhui Guo; Yong Yang; Bowen Bao; Xiaohong Zhang; Daochuan Zhang (Pesticide Biochemistry and Physiology, 2024)

Biomass-MOF composites in wastewater treatment, air purification, and electromagnetic radiation adsorption – A review - Jinxuan Jiang; Yang Shi; Mingjun Wu; Mashallah Rezakazemi; Tejraj M. Aminabhavi; Runzhou Huang; Chong Jia; Shengbo Ge (Chemical Engineering Journal, 2024)

Reduced internal stress of quasi-single crystalline Na4Fe3(PO4)2P2O7 electrode enhancing sodium-ion kinetics - Yukun Xi; Mingjun Wang; Guangjin Wang; Junqi Peng; Ningjing Hou; Zihao Yang; Xiaoxue Wang; Dongzhu Liu; Xiaohua Pu; Guiqiang Cao; Ruixian Duan; Qinting Jiang; et al. (Chemical Engineering Journal, 2024)

Improving Granulosa Cell Function in Premature Ovarian Failure with Umbilical Cord Mesenchymal Stromal Cell Exosome-Derived hsa_circ_0002021 - Ge Yang; Bo Zhang; Mei Xu; MingJun Wu; Jie Lin; ZiYu Luo; YueHua Chen; Qin Hu; GuoPing Huang; HaiYan Hu (Tissue Engineering and Regenerative Medicine, 2024)

Diesel exhaust particulate matter induces GC-1 spg cells oxidative stress by KEAP1-NRF2 pathway and inhibition of ATP5α1 S-sulfhydration - Jiayi Shi; Fang Tian; Jianke Ren; Runsheng Li; Mingjun Yang; Weihua Li (Food and Chemical Toxicology, 2024)

A Synthetic Steroid 5α-Androst-3β, 5, 6β-triol Alleviates Radiation-Induced Brain Injury in Mice via Inhibiting GBP5/NF-κB/NLRP3 Signal Axis - Ke Zhong; Kejia Liu; Yu Song; Sitai Chen; Xia Hu; Ruiqi Xue; Xueying Ma; Shaojian Li; Jingwen Yang; Zhenhong Deng; Xiaoqiu Zhu; Mingjun Yuan; et al. (Molecular Neurobiology, 2024)

Altitude effect of precipitation isotopes in an arid mountain-basin system: Observation and modelling around the world’s second-largest shifting desert - Shengjie Wang; Liwei Wang; Gahong Yang; Yanqiong Xiao; Athanassios A. Argiriou; Yudong Shi; Shijun Lei; Mingjun Zhang (Journal of Hydrology, 2024)

Reconstruction of Historical Metal Backgrounds in Lacustrine Environments of China Using an Anodonta woodiana “Specimen Bank” - Mingjun Yan; Xiubao Chen; Junren Xue; Hongbo Liu; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2024)

Degradation of petroleum hydrocarbon contaminants by Rhodococcus erythropolis KB1 synergistic with alfalfa (Medicago sativa L.) - Yan Nan; Ning Zhu; Shangchen Sun; Tianzhu Lei; Xiaopeng Guo; Feifan Leng; Mingjun Yang; Jixiang Chen; Yonggang Wang (Environmental Science and Pollution Research, 2024)

Monitoring fluid migration in a CO2 storage reservoir by distributed fiber optic strain sensing: A laboratory study - Jintao Xu; Chunlai Li; Menglan Shi; Xin Wang; Lanlan Jiang; Mingjun Yang; Yongchen Song (Gas Science and Engineering, 2024)

An organic acid-alkali coordinately regulated liquid electrolyte enables stable cycling of high-voltage proton battery - Huige Ma; Mingsheng Yang; Rui Li; Yan Wang; Liping Zheng; Xiaoming Jing; Yuxing Hao; Yujie Dai; Jiefeng Gao; Mingjun Hu; Jun Yang (Chemical Engineering Journal, 2024)

Interannual variations in stable isotopes of atmospheric water in arid Central Asia due to changes in atmospheric circulation - Shengjie Wang; Gahong Yang; John Bershaw; Xiaokang Liu; Kei Yoshimura; Yanqiong Xiao; Mingjun Zhang (Global and Planetary Change, 2024)

Enhanced thermophilic dark fermentation of hydrogen production from food waste by Fe-modified biochar - Yongjun Yang; Jie Bu; Yong Wei Tiong; Shuai Xu; Jingxin Zhang; Yiliang He; Mingjun Zhu; Yen Wah Tong (Environmental Research, 2024)

The effects of rhamnolipid on the formation of CH4 hydrate and separation of CH4/N2 via hydrate formation - Yi Zhang; Jingru Zhang; Xingang Xu; Wanting Liu; Yongsheng Xu; Mingjun Yang; Yongchen Song (Fuel, 2024)

Copper Stress Causes Shell Morphology Changes in Early Juvenile Anodonta woodiana Based on Geometric–Morphometric Analysis - Mingjun Yan; Xiubao Chen; Junren Xue; Hongbo Liu; Tao Jiang; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2024)

Characteristics of microplastic-derived dissolved organic matter and its binding with pharmaceuticals unveiled by fluorescence spectroscopy and two-dimensional correlation spectroscopy - Caixia Yan; Xiao Wang; Minghua Nie; Xiting Mo; Mingjun Ding; Jie Chen; Yi Yang (Science of The Total Environment, 2024)

Assessing the progress of the mining industry towards green growth in China: A three-stage dynamic network slacks-based measure approach - Liming Xue; Mingjun Li; Zhixue Zheng; Shiyu Xi; Yuheng Yang; Wenlei Yang; Qiwen Hou (Journal of Cleaner Production, 2024)

Heat risk assessment and response to green infrastructure based on local climate zones - Yang Xiang; Chao Yuan; Qingya Cen; Chunbo Huang; Changguang Wu; Mingjun Teng; Zhixiang Zhou (Building and Environment, 2024)

Genome dosage alteration caused by chromosome pyramiding and shuffling effects on karyotypic heterogeneity, reproductive diversity, and phenotypic variation in Zea–Tripsacum allopolyploids - Yingzheng Li; Xu Yan; Mingjun Cheng; Zizhou Wu; Qiyuan Zhang; Saifei Duan; Yong Zhou; Huaxiong Li; Shipeng Yang; Yulin Cheng; Wansong Li; Lulu Xu; et al. (Theoretical and Applied Genetics, 2024)

Ultralow thermal conductivity of robust vermiculite aerogels fabricated by fast trivalent cation induced nanosheet gelation - Changrui Shi; Wen Luo; Hongsheng Dong; Yang Zhang; Shuai Wang; Junjie Wang; Yongchen Song; Mingjun Yang; Yanghui Li; Zheng Ling (Chemical Engineering Journal, 2023)

Assessing nutritional and economic aspects of food loss and waste in China - Ruigang Wang; Shijun Lu; Lin Zhou; Zhenni Yang; Zhenchuang Tang; Mingjun Zhao; Guangyan Cheng (Sustainable Production and Consumption, 2023)

Reduced soil multifunctionality and microbial network complexity in degraded and revegetated alpine meadows - Bobo Wu; Mingjun Ding; Hua Zhang; Adam Thomas Devlin; Peng Wang; Lu Chen; Yueju Zhang; Yang Xia; Jiawei Wen; Linshan Liu; Yili Zhang; Minhuang Wang (Journal of Environmental Management, 2023)

Continuous measurement of gas permeability in non-homogeneous hydrate reservoirs under effective pressure via a novel apparatus - Guangjun Gong; Guojun Zhao; Weixin Pang; Mengru Tian; Bingbing Chen; Mingjun Yang; Yongchen Song (Gas Science and Engineering, 2023)

Temperature response mechanism of methane hydrate decomposition coupled with icing and melting under variational thermodynamic conditions - Mengru Tian; Yongchen Song; Weixin Pang; Jia-nan Zheng; Shuang Dong; Mingjun Yang (Fuel, 2023)

Preemptive QP001, a fast-acting meloxicam formulation, provides analgesia and reduces opioid consumption following abdominal surgery: a randomized controlled trial - Yingyong Zhou; Bin Wang; Kaiming Duan; Zhihong Bai; Xianwen Hu; Mingjun Xu; Xiaohong Li; Yuanli Gao; Jiangang Li; Mengchang Yang; Ying Zhang; Wei Zhang; et al. (Inflammopharmacology, 2023)

Investigating the electrochemical performance of MnO2 polymorphs as cathode materials for aqueous proton batteries - Yujie Dai; Jianze Zhang; Xiaorong Yan; Guoqing Zhao; Mingsheng Yang; Jiakui Xiong; Rui Li; Naihua Miao; Haiping Yu; Mingjun Hu; Jingru Liu; Jun Yang (Chemical Engineering Journal, 2023)

Surface urban heat island mitigation network construction utilizing source-sink theory and local climate zones - Yang Xiang; Qingya Cen; Chucai Peng; Chunbo Huang; Changguang Wu; Mingjun Teng; Zhixiang Zhou (Building and Environment, 2023)

Highly efficient photocathodic cascade material for constructing sensitive photoelectrochemical biosensor - Mingjun Xiao; Qian Xiong; Chaoju Yang; Hanmei Deng; Ruo Yuan; Yali Yuan (Analytica Chimica Acta, 2023)

CO2 capture performance of CaO-based sorbent modified with torrefaction condensate during calcium looping cycles - Chongcong Li; Xingli Gong; Hao Zhang; Yan Zhang; Mingjun Yang; Bingbing Chen (Chemical Engineering Journal, 2023)

How can blockchain technology promote food safety in agricultural market?—an evolutionary game analysis - Yanhu Bai; Zhuodong Yang; Minmin Huang; Mingjun Hu; Shiyu Chen; Jianli Luo (Environmental Science and Pollution Research, 2023)

4.3% efficient kesterite solar cell modules - Mingjun Yuan; Chunxu Xiang; Zhen Yan; Hongfei Zhou; Naiyun Liu; Shuxia Wei; Wei Li; Weibo Yan; Chunlei Yang; Hao Xin (Science Bulletin, 2023)

Octyl gallate targeting the 3C-like protease exhibits highly efficient antiviral activity against swine enteric coronavirus PEDV - Mingjun Su; Baishuang Yin; Xiaoxu Xing; Zijian Li; Jiyu Zhang; Shufeng Feng; Lu Li; Feiyu Zhao; Xu Yang; Shiping Yu; Jun Wang; Yongchen Zhang; et al. (Veterinary Microbiology, 2023)

Impact of body fat and fitness on human thermal responses under transient neutral-cool indoor conditions - Mingjun Zhang; Lijuan Wang; Jie Yang; Faming Wang; Ji Yang; Weimin Pan; Yi Xu (Building and Environment, 2023)

Joint-production characteristics of typical marine composite reservoir with water-saturated methane hydrates and higher-pressure gas by depressurization - Jia-nan Zheng; Jie Zhao; Ying Teng; Xinru Wang; Mingjun Yang (Gas Science and Engineering, 2023)

Quantifying food loss along the animal products supply chain in China with large-scale field-survey based primary data - Ruigang Wang; Gang Liu; Lin Zhou; Zhenni Yang; Zhenchuang Tang; Shijun Lu; Mingjun Zhao; Huiwu Sun; Chuang Ma; Guangyan Cheng (Resources, Conservation and Recycling, 2023)

Pyrolytic aerogels with tunable surface groups for efficient methane solidification storage via gas hydrates - Changrui Shi; Shuai Wang; Huiquan Liu; Lunxiang Zhang; Mingjun Yang; Yongchen Song; Jiafei Zhao; Zheng Ling (Fuel, 2023)

Maternal exposure to ambient PM2.5 perturbs the metabolic homeostasis of maternal serum and placenta in mice - Shimin Tao; Mingjun Yang; Bin Pan; Yuzhu Wang; Fang Tian; Dongyang Han; Wenpu Shao; Wenhui Yang; Yuanting Xie; Xinyi Fang; Minjie Xia; Jingying Hu; et al. (Environmental Research, 2023)

Comprehensive proteomic and phosphoproteomic reveal that Microcystin-LR contributed to the malignant progression of gastric cancer by estrogenic potency - Peiyan Yang; Peng Zhang; Yali Deng; Yinghao Liao; Xinxin Guo; Mingjun Sun; Lihong Yin; Ran Liu (Environmental Pollution, 2023)

Host Fish Suitability for Freshwater Bivalve Anodonta woodiana Breeding Programs - Xiubao Chen; Guochao Duan; Mingjun Yan; Hongbo Liu; Tao Jiang; Jian Yang (Fishes, 2022)
The freshwater bivalve Anodonta woodiana is native to China and widely distributed in Asia, Europe, and North America. However, natural populations of A. woodiana in China have dramatically declined recently. Several fish species have been used as potential hosts in breeding programs; nonetheless, the optimal host species is yet to be identified. In this study, we examined the suitability of five potential host fish species (bighead carp, common carp, crucian carp, yellow catfish, and tilapia) for A. woodiana under laboratory conditions. No significant difference was found in the number of glochidia attached to the five fish species; however, tilapia hosted more transformed juveniles than bighead carp, common carp, or yellow catfish (p

Optimized structural parameters and heat extraction capacity of a mixing device for constant pressure CO2 mineralization using alkaline waste - Wei Lu; Yang Yuan; Xiangming Hu; Guansheng Qi; Lulu Sun; Maoyuan Zhang; MingJun Wang; Min He (Environmental Science and Pollution Research, 2022)

Short-term exposure to six air pollutants and cause-specific cardiovascular mortality of nine counties or districts in Anhui Province, China - Guoao Li; Huanhuan Zhao; Mingjun Hu; Jialiu He; Wanjun Yang; Hanshuang Zhang; Zhenyu Zhu; Jinliang Zhu; Fen Huang (Environmental Science and Pollution Research, 2022)

Effects of carbon dioxide and green space on sleep quality of the elderly in rural areas of Anhui Province, China - Guoao Li; Zhenyu Zhu; Mingjun Hu; Jialiu He; Wanjun Yang; Jinliang Zhu; Huanhuan Zhao; Hanshuang Zhang; Fen Huang (Environmental Science and Pollution Research, 2022)

Genetic variation and differentiation of Quercus variabilis populations at phosphate and non-phosphate rock sites in southwestern China - Huawei Ji; Baoming Du; Hongmei Du; Ningxiao Sun; Xu Yang; Mingjun Peng; Hongzhang Kang; Shan Yin; Chunjiang Liu (Plant Systematics and Evolution, 2021)

A Hu sheep genome with the first ovine Y chromosome reveal introgression history after sheep domestication - Ran Li; Peng Yang; Ming Li; Wenwen Fang; Xiangpeng Yue; Hojjat Asadollahpour Nanaei; Shangquan Gan; Duo Du; Yudong Cai; Xuelei Dai; Qimeng Yang; Chunna Cao; et al. (Science China Life Sciences, 2021)

Study on Interaction of Coomassie Brilliant Blue G-250 with Bovine Serum Albumin by Multispectroscopic - Mingjun Yang; Dongxiang Shi; Yonggang Wang; Abdol Ghaffar Ebadi; Mohsen Toughani (International Journal of Peptide Research and Therapeutics, 2021)

High-throughput Sequencing-based Analysis of Microbial Diversity in Rice Wine Koji from Different Areas - Xinxin Zhao; Yurong Wang; Wenchao Cai; Mingjun Yang; Xiaodan Zhong; Zhuang Guo; Chunhui Shan (Current Microbiology, 2020)

The protective function of non-coding DNA in DNA damage accumulation with age and its roles in age-related diseases - Guo-Hua Qiu; Xintian Zheng; Mingjun Fu; Cuiqin Huang; Xiaoyan Yang (Biogerontology, 2019)

Recent Progress in Dual-Polarization Radar Research and Applications in China - Kun Zhao; Hao Huang; Mingjun Wang; Wen-Chau Lee; Gang Chen; Long Wen; Jing Wen; Guifu Zhang; Ming Xue; Zhengwei Yang; Liping Liu; Chong Wu; et al. (Advances in Atmospheric Sciences, 2019)

Allopolyploidization facilitates gene flow and speciation among corn, Zea perennis and Tripsacum dactyloides - Muhammad Zafar Iqbal; Mingjun Cheng; Yuegui Su; Yang Li; Weiming Jiang; Huaxiong Li; Yanli Zhao; Xiaodong Wen; Lei Zhang; Asif Ali; Tingzhao Rong; Qilin Tang (Planta, 2019)

Cloning, Expression, and Bioinformatics Analysis of Heavy Metal Resistance Gene afe_1862 from Acidithiobacillus ferrooxidans L1 in Escherichia coli - Feifan Leng; Yuanli Li; Wen Luo; Qingwei Wei; Yanjun Jing; Xiaoli Wang; Mingjun Yang; Yonggang Wang (Biological Trace Element Research, 2019)

Displacement and Dissolution Characteristics of CO $$_{2}$$ 2 /Brine System in Unconsolidated Porous Media - Lanlan Jiang; Minghao Yu; Ying Teng; Mingjun Yang; Yu Liu; Weizhong Li; Yongchen Song (Transport in Porous Media, 2018)

Human biomonitoring of eight trace elements in urine of residents living in rural areas along the Yangtze River, China - Yanjie Cui; Qi Zhong; Mingjun Hu; Jie Sheng; Yuanyuan Yang; Ling Liang; Xiaodong Wang; Yuwei Yang; Mengmeng Zhou; Fen Huang (Environmental Science and Pollution Research, 2017)

The Effect of Divalent Metal Ions and Recycle Ratio of UASB Reactor on the Formation of Anammox Granules and Its Treatment Performance - Jinxiang Fu; Mingjun Zhou; Jie Yun; Yang Su; Pengfei Yu; Ming Sun; Xinqi Ji (Water, Air, & Soil Pollution, 2017)

Dynamic change of the rhizosphere microbial community in response to growth stages of consecutively monocultured Rehmanniae glutinosa - Qingxiang Yang; Ruifei Wang; Yuanyuan Xu; Chunxiao Kang; Ying Miao; Mingjun Li (Biologia, 2016)

BAC mediated transgenic Large White boars with FSHα/β genes from Chinese Erhualian pigs - Pan Xu; Qiuyan Li; Kai Jiang; Qiang Yang; Mingjun Bi; Chao Jiang; Xiaopeng Wang; Chengbin Wang; Longyun Li; Chuanmin Qiao; Huanfa Gong; Yuyun Xing; et al. (Transgenic Research, 2016)

Characterization, expression and silencing by RNAi of p53 from Penaeus monodon - Wenting Dai; Lihua Qiu; Chao Zhao; Mingjun Fu; Zhenhua Ma; Falin Zhou; Qibin Yang (Molecular Biology Reports, 2016)

The effect of different genome and cytoplasm on meiotic pairing in maize newly synthetic polyploids - Mingjun Cheng; Mingmin Zheng; Shipeng Yang; Yang Li; Xingchun Dong; Jing Li; Rulong Sun; Huaxiong Li; Shufeng Zhou; Yuanqi Wu; Tingzhao Rong; Qilin Tang (Euphytica, 2016)
Allopolyploidization plays the special role in the evolution of many crops. Moreover, the evolution in early stage of some allopolyploidization events is predicted to be effected by nuclear-cytoplasmic interactions. Maize and teosintes are well model system for study of genetic recombination in allopolyploidization. In order to investigate the effects of genome organization and cytoplasm on genome evolution in newly synthesized allopolyploids (neoallopolyploids), a series of neoallopolyploids were produced by reciprocal crosses of maize and Zea perennis . By using dual-color genomic in situ hybridization, intra- and intergenomic meiosis pairing of these polyploids were quantified and compared with regard to its genome organization and cytoplasm background. In the four neoallopolyploids, the stability of maize genome is consistently lower than that of Z. perennis genome. Additional, the stability of maize genome is affected by genome ploidy. The cytoplasm, genome composition and their interaction do have the special role in chromosome paring and the meiosis behaviors in Zea allopolyploids vary significantly and showed non-diploidization. Z. perennis cytoplasm may give a relatively relaxed environment for maize genome.

Supplementary studies on Myxobolus tsangwuensis Chen, 1954 (Myxozoa: Myxosporea) infecting the gills of common carp Cyprinus carpio (L.): molecular and histological data - Mingjun Huang; Yang Liu; Luo Jia; Yanhua Zhai; Qiong Deng; Zemao Gu (Acta Parasitologica, 2014)
Myxobolus tsangwuensis Chen, 1954 is a common parasite infecting the gills of common carp Cyprinus carpio (L.). It was described simply in the original description and its molecular data was absent, which makes the accurate diagnosis challenging. Here we supplemented its description based on the morphological, histological and molecular data. It was characterized by the presence of small round or ellipsoidal plasmodia in the gills of host and histology showed the plasmodia developed in the capillary network of the gill lamella. Mature spores of M. tsangwuensis were ellipsodal in frontal view and lemon shaped in lateral view, averaging 11.2 ± 0.7 (10.2–12.5) μm × 9.3 ± 0.3 (8.5–10.0) μm × 6.2 ± 0.4 (5.5–7.0) μm. Spores valves were symmetrical and smooth. Occasionally, a small intercapsular appendix was observed. Two polar capsules were pyriform with different sizes, measuring 5.0 ± 0.2 (4.4–5.3) μm × 3.1 ± 0.1 (2.9–3.5) μm and 3.9 ± 0.2 (3.4–4.3) μm × 2.5 ± 0.2 (2.0–2.8) μm, respectively. Polar filaments coiled five to seven turns in large polar capsule and three to four turns in the small polar capsule. Some spores were surrounded by the mucous envelope that was not recorded in the original description. Molecular analysis revealed that the present SSU rDNA sequences did not match any available sequences in GenBank and phylogenetic analysis showed M. tsangwuensis was sister to M. basilamellaris and M. musseliusae.

In-situ observation for formation and dissociation of carbon dioxide hydrate in porous media by magnetic resonance imaging - ChuanXiao Cheng; JiaFei Zhao; YongChen Song; ZiHao Zhu; WeiGuo Liu; Yi Zhang; MingJun Yang; XiChong Yu (Science China Earth Sciences, 2013)

A natural mutation-led truncation in one of the two aluminum-activated malate transporter-like genes at the Ma locus is associated with low fruit acidity in apple - Yang Bai; Laura Dougherty; Mingjun Li; Gennaro Fazio; Lailiang Cheng; Kenong Xu (Molecular Genetics and Genomics, 2012)

Acetylcholinesterase inhibitory activity of the total alkaloid from traditional Chinese herbal medicine for treating Alzheimer’s disease - Zhongduo Yang; Dongbo Zhang; Jin Ren; Mingjun Yang; Shuo Li (Medicinal Chemistry Research, 2012)

The conditioned medium from a stable human GDF3-expressing CHO cell line, induces the differentiation of PC12 cells - Qiang Li; Xianghua Liu; Yanhua Wu; Jian An; Saiyin Hexige; Yichen Ling; Mingjun Zhang; Xianmei Yang; Long Yu (Molecular and Cellular Biochemistry, 2012)

Functional characterization of the promoter region of human TNFAIP1 gene - Mingjun Liu; Zhenhua Sun; Aidong Zhou; Hong Li; Liping Yang; Chang Zhou; Rushi Liu; Xiang Hu; Jianlin Zhou; Shuanglin Xiang; Jian Zhang (Molecular Biology Reports, 2010)

Vegetation change in the Mt. Qomolangma Nature Reserve from 1981 to 2001 - Wei Zhang; Yili Zhang; Zhaofeng Wang; Mingjun Ding; Xuchao Yang; Xuedong Lin; Linshan Liu (Journal of Geographical Sciences, 2007)

Climate change in Mt. Qomolangma region since 1971 - Xuchao Yang; Yili Zhang; Wei Zhang; Yuping Yan; Zhaofeng Wang; Mingjun Ding; Duo Chu (Journal of Geographical Sciences, 2006)